Mollusc and brachiopod skeletal hard parts: Intricate archives of their marine environment. Issue 1 (January 2016) - Immenhauser, Adrian; Schöne, Bernd R.; Hoffmann, René; Niedermayr, Andrea
Abstract: The biogenic carbonate hard parts of fossil bivalves, cephalopods and brachiopods are among the most widely exploited marine archives of Phanerozoic environmental and climate dynamics research. The advent of novel analytical tools has led many workers to explore non‐traditional geochemical and petrographic proxies, and work performed in neighbouring disciplines sheds light on the complex biomineralization strategies applied by these organisms. These considerations form a strong motivation to review the potential and problems related to the compilation and interpretation of proxy data from bivalve, cephalopod and brachiopod hard parts from the viewpoint of the sedimentologist and palaeoceanographer. Specific focus is on the complex biomineralization pathways of a given dissolved ion or food particle from its aquatic environment via the digestion and biomineralization apparatus in molluscs and brachiopods and its incorporation into a biomineral. Given that molluscs and brachiopods do not secrete their hard parts from seawater but rather from their mantle and periostracum, this paper evaluates differences and similarities of seawater versus that of body fluids. Cephalopods, bivalves and brachiopods exert a strong biological control on biomineralization that, to some degree, may buffer their shell geochemistry against secular changes in seawater chemistry. Disordered (amorphous) calcium carbonate precursor phases, later transformed to crystalline biominerals, may be significant in carbonate archive research due to expected geochemical offset relative to the direct precipitation of stable phases. A reasonable level of understanding of the related mechanisms is thus crucial for those who use these skeletal hard parts as archives of the palaeo‐environment. The impact of what is commonly referred to as 'biological factors' on the geochemistry of mollusc and brachiopod hard parts is explored for conventional isotope systems such as carbon, oxygen, strontium and traditionally used element to calcium ratios. In particular, the often used δ 13 Ccarb or the Mg/Ca and Sr/Ca elemental proxies are fraught with problems. An interesting new research field represents the analysis, calibration and application of non‐traditional proxies to mollusc and brachiopod hard parts. Examples include the carbonate clumped isotope (Δ47 ) approach and the analysis of the isotopes of Ca, Mg, N, Li, S or element to Ca ratios such as Li/Ca or B/Ca and rare earth elements. Based on considerations discussed here, a series of " do's and don'ts " in mollusc and brachiopod archive research are proposed and suggestions for future work are presented. In essence, the suggestions proposed here include experimental work (also field experiments) making use of recent archive organisms or, where possible, a reasonable recent analogue in the case of extinct groups. Moreover, the detailed understanding of the architecture of mollusc and brachiopod hard parts and their ultra‐structures must guide sampling strategies for geochemical analyses. Where feasible, a detailed understanding of the diagenetic pathways and the application of multi‐proxy and multi‐archive approaches should form the foundation of fossil carbonate archive research. The uncritical compilation of large data sets from various carbonate‐shelled organisms collected at different locations is not encouraged.